Persepsi Siswa Pada Guru Bk Terhadap Intensitas Mendatangi Guru BK Di MTs. Satu Atap (SA) Miftahul Ulum Sodong Panti - Ma’ruf, Ma’ruf; Swastinah, Titin; Novianti , Ade Irma (FKIP Universitas Islam Jember, 2020)
Research on the Effect of Student Perceptions on BK Teachers on Intensity of Visiting Buru Bk MTs SA Miftahul Ulum Sodong Kemiri Panti Academic Year 2013/2014 with 83 students as respondents. In this study were all students from grades VII, VIII, and IX of MTs SA Miftahul Ulum Sodong Kemiri Panti Jember. In this study, all 83 students will become respondents so this study uses census research. This type of research is quantitative because in this study the influence of students' perceptions of BK teachers on the intensity level of visiting Bk teachers. The data obtained needs to be processed and analyzed further in order to obtain accurate data by using the product moment correlation analysis technique. By matching the values ​​in the product moment coefficient table for the value of N = 83 with a significant level of 95% of 0.217, while for 99% it is 0.282, while the results obtained from the calculation of the table above are 0.892, so r count is above the level significance of 95% and 99%. Thus, it can be concluded that the hypothesis which states